Status of Tigers Outside the Protected Areas in Mizoram - Patnaik, S. S. (Indian Forester, 1999)
In this paper, the status of Tiger outside Protected Areas (PAs) in Mizoram has been highlighted. The hilly terrain with dense and open. forests forms an ideal habitat for Tiger. Administrative and financial constraints in P A management are pointed out and strategies for effective conservation of Tiger population outside PAs are discussed.